The science of art : optical themes in western art from Brunelleschi to Seurat - Kemp, Martin; Yale University Press (New Haven : Yale University Press, 1990)
For almost five hundred years the central goal of European painting was the imitation of nature. Many artist and theorists, believing that imitation must be based on scientific principles, found inspiration or guidance in two branches of optics--the geometrical science of perspective and the physical science of colour. In this pathbreaking and highly illustrated book Martin Kemp examines the major optically orientated examples of artistic theory and practice from the Renaissance to the nineteenth century.
INTRODUCTION ---- PART I: LINES OF SIGHT. Introduction to Part I --- 1. Perspective from Brunelleschi to Leonardo --- 2. Perspective from Durer to Galileo --- 3. Perspective from Rubens to Turner ---- PART II: MACHINE AND MIND. Introduction to Part II --- 4. Machines and marvels --- 5. Seeing, knowing and creating ---- PART III: THE COLOUR OF LIGHT. Introduction to Part III --- 6. The Aristotelian legacy --- 7. Newton and after --- Colour plates --- Coda ---- APPENDIX I. EXPLANATION OF LINEAR PERSPECTIVE --- APPENDIX II. BRUNELLESCHI'S DEMONSTRATION PANELS.
Includes bibliographical references (pages 363-364) and index.
Keywords: Painting -- Technique; Composition (Art); Perspective; Color in art; Nature (Aesthetics)